When lying changes memory for the truth. Issue 1 (2nd January 2018) - Otgaar, Henry; Baker, Alysha
ABSTRACT: In the legal field, victims and offenders frequently lie to avoid talking about serious incidents, such as past experiences of sexual abuse or criminal involvement. Although these individuals may initially lie about an experienced event, oftentimes these same people eventually abandon their lies and are forthcoming with what truly happened. To date, it is unclear whether such lying affects later statements about one's memory for the experienced event. The impetus of the present review is to compile the current state of knowledge on the effects of lying on memory. Based on existing literature, we will describe how deceptive strategies (e.g., false denials) regarding what is remembered may affect memory in consequential ways, such as forgetting of details, falsely remembering features that were not present, or a combination of both. It will be argued that the current literature suggests that mnemonic outcome is contingent on the type of lie and we will propose a theoretical framework outlining which forms of lying likely result in certain memory outcomes. Potential avenues of future research also will be discussed.